2010
DOI: 10.1161/strokeaha.110.578369
|View full text |Cite
|
Sign up to set email alerts
|

Systemic and Intraplaque Mediators of Inflammation Are Increased in Patients Symptomatic for Ischemic Stroke

Abstract: Background and Purpose-The concept of "vulnerable plaque" has been extended to the more recent definition of the "cardiovascular vulnerable patient," in which "intraplaque" and "systemic" factors contribute to the cumulative risk of acute cardiovascular events. Thus, we investigated the possible role of systemic and intraplaque inflammation in patients asymptomatic versus symptomatic for ischemic stroke. Methods-Regions upstream and downstream the blood flow were isolated from internal carotid plaques of patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
124
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 108 publications
(136 citation statements)
references
References 30 publications
11
124
1
Order By: Relevance
“…12 Accordingly, high neutrophil numbers have been recently associated with features of rupture-prone carotid plaques, that is, large lipid core, high macrophage numbers, and low collagen amount and SMC numbers. 14,38 Presence of neutrophils in murine atherosclerotic plaques has been confirmed in various experimental studies including our own. 28,39 Among other possible proatherogenic mechanisms, neutrophils have been recently shown to deposit cathelicidins (in mice known as cathelin-related antimicrobial peptide, [CRAMP]) on inflamed arterial endothelium, thereby promoting the recruitment of inflammatory monocytes.…”
Section: Discussionsupporting
confidence: 66%
“…12 Accordingly, high neutrophil numbers have been recently associated with features of rupture-prone carotid plaques, that is, large lipid core, high macrophage numbers, and low collagen amount and SMC numbers. 14,38 Presence of neutrophils in murine atherosclerotic plaques has been confirmed in various experimental studies including our own. 28,39 Among other possible proatherogenic mechanisms, neutrophils have been recently shown to deposit cathelicidins (in mice known as cathelin-related antimicrobial peptide, [CRAMP]) on inflamed arterial endothelium, thereby promoting the recruitment of inflammatory monocytes.…”
Section: Discussionsupporting
confidence: 66%
“…In addition, these authors showed that neutrophilic inflammation positively correlated with the early atherogenesis in hypercholesterolemic (Ldlr Ϫ/Ϫ ) mice (3). On the other hand, neutrophil infiltration within atherosclerotic plaques has also been shown to be strongly associated with plaque vulnerability in humans (8,16). Our research approach was further supported by the recent discovery of the potential "pleiotropic" activities of acipimox through the binding with its receptor GPR109 (12,30,34).…”
Section: Discussionsupporting
confidence: 52%
“…Our research approach was further supported by the recent discovery of the potential "pleiotropic" activities of acipimox through the binding with its receptor GPR109 (12,30,34). High levels of recombinant insulin have previously been shown to induce neutrophil recruitment toward the proinflammatory CC chemokine CCL3 that is expressed in atherosclerotic plaques (14,16). In addition, insulin-induced neutrophil locomotion to CCL3 was associated with the activation of intracellular JNK1/2 (14).…”
Section: Discussionmentioning
confidence: 79%
“…The inflammatory paradigm has represented an important achievement in the understanding of the atherosclerotic process: abundant laboratory and clinical evidence accumulated over the last twenty years, also from our research group (Montecucco et al 2010), confirming the hypothesis that inflammation exerts a major role through the different stages of atherosclerosis (Ross, 1999;Hansson, 2005;Hansson & Libby, 2006;Libby et al, 2009). Therefore it would be interesting to evaluate how the therapeutic choices exerted by physicians can modulate the inflammatory activation (the so called pleiotropic effects): in other terms do the drugs we use in the attempt of counteracting atherosclerosis (such as anti-hypertensive drugs, statins, fibrates, aspirin, anti-diabetic drugs) exert their protective effects through their main site of action (decrease of blood pressure, cholesterol, triglycerides, and glucose, anti-platelets actions) or can an additional anti-inflammatory effect be proposed, at least for some of them?…”
Section: Introductionsupporting
confidence: 56%